Empagliflozin: a new sodium-glucose co-transporter 2 (SGLT2) inhibitor for the treatment of type 2 diabetes - Neumiller, Joshua J (Just Medical Media Limited, 2014)
Type 2 diabetes is increasing in prevalence worldwide, and hyperglycemia is often poorly controlled despite a number of therapeutic options. Unlike previously available agents, sodium-glucose co-transporter 2 (SGLT2) inhibitors offer an insulin-independent mechanism for improving blood glucose levels, since they promote urinary glucose excretion (UGE) by inhibiting glucose reabsorption in the kidney. In addition to glucose control, SGLT2 inhibitors are associated with weight loss and blood pressure reductions, and do not increase the risk of hypoglycemia. Empagliflozin is a selective inhibitor of SGLT2, providing dose-dependent UGE increases in healthy volunteers, with up to 90 g of glucose excreted per day. It can be administered orally, and studies of people with renal or hepatic impairment indicated empagliflozin needed no dose adjustment based on pharmacokinetics. In Phase II trials in patients with type 2 diabetes, empagliflozin provided improvements in glycosylated hemoglobin (HbA1c) and other measures of glycemic control when given as monotherapy or add-on to metformin, as well as reductions in weight and systolic blood pressure. As add-on to basal insulin, empagliflozin not only improved HbA1c levels but also reduced insulin doses. Across studies, empagliflozin was generally well tolerated with a similar rate of hypoglycemia to placebo; however, patients had a slightly increased frequency of genital infections, but not urinary tract infections, versus placebo. Phase III studies have also reported a good safety profile along with significant improvements in HbA1c, weight and blood pressure, with no increased risk of hypoglycemia versus placebo. Based on available data, it appears that empagliflozin may be a useful option in a range of patients; however, clinical decisions will be better informed by the results of ongoing studies, in particular, a large cardiovascular outcome study (EMPA-REG OUTCOME™).